Examining the Deviation From Balanced Time Perspective in the Dark Triad Throughout Adulthood - Birkás, Béla; Matuz, András; Csathó, Árpád (Frontiers in Psychology, 2018)
Individuals who score high on Dark Triad (DT) personality traits (i.e. Machiavellianism, subclinical narcissism and subclinical psychopathy) have been found to prefer a fast life strategy with enhanced motivation for immediate resource acquisition and short-term benefits. In line with these points, recent studies have found evidence showing that DT traits are associated with a biased, strongly present-oriented time perspective. In the current study, we aimed to examine whether the temporal attitude of individuals high in DT is deviant from a balanced time perspective (BTP) to a significant extent. To achieve this aim, we applied two operationalizations published in earlier studies to quantify BTP: the Deviation from Balanced Time Perspective coefficient (DBTP), calculated as the difference between individuals' time perception and the optimal time perspective, as well as the person-oriented approach of identifying groups of individuals with similar time perception. Importantly, the age of participants (N = 346) covered a long and continuous period of adulthood—from the young adulthood to the elderly—in order to examine the moderating effect of age on the association of DT and BTP. Machiavellianism and psychopathy were both found to be clearly deviant from a BTP. In contrast, higher scores on narcissism were positively associated with a balanced time perspective profile. The DBTP analysis, however, suggested that this beneficial effect of narcissism was only prevalent among the elderly individuals.